COMUNICAREA ŞTIINŢEI LA BIBLIOTECA „TÂRGU-MUREŞ”, ADRESATĂ DIVERSELOR GRUPURI DE CITITORI - ŞATRAVCA, bibliotecar principal, Filiala „Târgu-Mureş”, Tatiana (BIBLIOPOLIS, 2020)
One of the objectives of the Library „Targu- Mures” is to promote scientific literature to various user’s groups. For this purpose the library used different methods and forms of communication of science: book exhibitions, book presentations, roundtables, creative competitions, discussions debates, meetings with personnalities, public lectures, sociological researches on the science topic. The library scientific activities are promoted on blogs and social networking.